PERANCANGAN SISTEM PEMANTAUAN SUHU UDARA DAN KELEMBABAN UDARA STASIUN METEOROLOGI SULTAN HASANUDDIN MAROS - Anugraha, Nurhajar; Angriawan, Randy (JURNAL TELISKA, 2023)
Internet of Things (IoT) is a concept to integrate and connect all electronic devices using the internet network, so that they can develop such as smart homes, smart buildings, and more complex ones, such as smart cities. The purpose of this research is to design a monitoring system for air temperature and humidity using NodeMCU as a controller with DHT11, DHT22 sensors and a monitoring system using a web-based platform. This system integrates internet and cellular communication which will be sent via a microcontroller to the website so that it can be monitored remotely and as a backup line when the internet connection is having problems, researchers can view data via cellular or SMS. As result, Where after designing and testing the tool, the two sensors can function properly by displaying results that are not much different from monitoring using conventional methods. Key words : IoT, Monitoring, Temperature, Sensor